Marine biodiversity of areas beyond national jurisdiction - Nordquist, Myron H.; Long, Ronâan (Center for oceans law and policy, 2021)
"This book is based on presentations made at the Malmèo Conference by many of the most knowledgeable experts on both the on-going bbnj negotiations at the United Nations and on the well- established UNCLOS principles and rules. The Malmèo Conference featured remarks by distinguished diplomats followed by six parts devoted to identifying the major issues at the bbnj negotiations"--